Pengaruh Konseling Laktasi terhadap Pemberian ASI Eksklusif dan Tumbuh Kembang Anak - Desi Hariani; Meta Rosdiana (Jurnal Kebidanan Harapan Ibu Pekalongan, 2026)
Exclusive breastfeeding is one of the efforts to improve children's nutritional status in the first 1000 days of life (HPK).Currently, data from the Central Statistics Agency shows that the number of working mothers in Indonesia has reached 52.74 million people working in various sectors. Lactation counseling is a factor that can support exclusive breastfeeding because it can increase the knowledge and attitudes of pregnant women. This study aims to determine the effect of lactation counseling on knowledge, attitudes, and breastfeeding practices for 6 months. The type of research used is a quasi-experiment. The population and sample in this study were all pregnant women who came to the Kenanga health center in Kenten Village to undergo antenatal care. Data collection was collected by conducting interviews using questionnaires. Data analysis was performed by analysis using chi square test and multivariate analysis by logistic regression. The research results show that there is an influence of lactation counseling with breastfeeding with an Od Ratio value of 0.001 and there is an influence between knowledge and breastfeeding with a niai od Ratio of 0.004 which is smaller than the chi sqaure value of 0.05. This research is expected to improve performance use.